PROGRAM NAWACITA DALAM PERSPEKTIF PERPUSTAKAAN PERGURUAN TINGGI DI INDONESIA - Lilik Kurniawati Uswah (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
Inaccordance with nawacita, to which jokowi-jk's synergy refer to, the library ini Indonesia need to do so. Need to do so and support the program.The development of many countries are always indicated by the ability to respond the change with its new need, challenge, and treatment. This ability developed because there are libraries in educational institution. This libraries recognize and transform and share the knowledge, technology, and so do good literacy. University library should be as basic and center of intellectual, literacy, and knowledge. It is needed to strengthen the library univetsity as the infrastructure of three basic service of the university to develop the reputation of the university and ITS achievement.The university representatif library can be as the center of development of the country include Indonesia.